2014
DOI: 10.1038/srep05075
|View full text |Cite
|
Sign up to set email alerts
|

Polarization fatigue of organic ferroelectric capacitors

Abstract: The polarization of the ferroelectric polymer P(VDF-TrFE) decreases upon prolonged cycling. Understanding of this fatigue behavior is of great technological importance for the implementation of P(VDF-TrFE) in random-access memories. However, the origin of fatigue is still ambiguous. Here we investigate fatigue in thin-film capacitors by systematically varying the frequency and amplitude of the driving waveform. We show that the fatigue is due to delamination of the top electrode. The origin is accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 24 publications
6
53
0
Order By: Relevance
“…It was found that the P(VDF-TrFE) capacitors retained 70% of the initial polarization even after 6 Â 10 4 cycles. These data are consistent with previously reported fatigue behaviors [24][25][26][27][28][29][30]. An internal electric field created by the trapped charges acts opposite to the external electric field, causing an apparent increase in the switching voltage for the ferroelectric domains in P(VDF-TrFE) [31].…”
Section: Electrical Characteristics Of P(vdf-trfe) Capacitors Preparesupporting
confidence: 92%
“…It was found that the P(VDF-TrFE) capacitors retained 70% of the initial polarization even after 6 Â 10 4 cycles. These data are consistent with previously reported fatigue behaviors [24][25][26][27][28][29][30]. An internal electric field created by the trapped charges acts opposite to the external electric field, causing an apparent increase in the switching voltage for the ferroelectric domains in P(VDF-TrFE) [31].…”
Section: Electrical Characteristics Of P(vdf-trfe) Capacitors Preparesupporting
confidence: 92%
“…After 10 5 cycles the polarization decreased by a factor two as compared to the initial value ( Figure S13, Supporting Information). Together with the remnant polarization, coercive field, polarization switching time, and data retention being already comparable to the performance of P(VDF:TrFE) thin film devices, [57][58][59][60][61] this makes BTA-C6 interesting not only from a scientific, but also from an application point of view.…”
Section: Wwwadvelectronicmatdementioning
confidence: 93%
“…All measurements are highly reproducible as we carefully avoided fatigue, which for P(VDF-TrFE) is extrinsic, dominated by delamination of the top electrode. 40 Furthermore, within the time frame of the measurements, fatigue of PZT can be disregarded. 41,42 We note that a protocol for deterministic switching between any intermediate states can always be derived based on measured transients of polarization reversal, irrespective of the details of the switching mechanism.…”
mentioning
confidence: 99%